Lessons from the SARS-CoV-2 Pandemic: Perspectives in the Medico-Legal Field - Rosario Barranco; Andrea Molinelli; Gabriele Rocca; Francesco Ventura (Forensic Sciences)
Background: The SARS-CoV-2 pandemic led to an enormous global health, social and economic crisis. The pandemic caused considerable upheaval and considerable difficulties due to an unforeseen and devastating health condition. Materials and Methods: We discuss the numerous challenges encountered in the fields of forensic medicine and public health during the COVID-19 pandemic. Particularly during the first wave of the pandemic, forensic pathologists faced significant difficulties due to the lack of safe autopsy protocols and insufficient personal protective equipment. Mainly in Europe, they had to manage a substantial number of potential cases of medical liability related to COVID-19. The widespread outbreak of the virus in residential care homes and prisons posed another significant challenge. Furthermore, forensic pathologists had to address the issue of complications arising from vaccination campaigns. Conclusions: This article underscores the need for continued efforts in scientific research and healthcare preparedness to effectively manage such complex crises. Forensic pathologists must be equipped with the necessary resources and training to address unpredictable, complex situations with far-reaching social implications.